Risk Factors and Consequences of Lower Extremity Fracture Nonunions in Veterans With Spinal Cord Injury. (5th January 2022) - Sinnott, Bridget; Ray, Cara; Weaver, Frances; Gonzalez, Beverly; Chu, Elizabeth; Premji, Sarah; Raiford, Mattie; Elam, Rachel; Miskevics, Scott; Parada, Stephen; Carbone, Laura
ABSTRACT: We used Veterans Health Administration (VHA) national administrative data files to identify a cohort (fiscal years 2005–2014) of veterans with spinal cord injuries and disorders (SCID) to determine risk factors for and consequences of lower extremity fracture nonunions. Odds ratios (OR) for fracture nonunion were computed using multivariable‐adjusted logistic regression models. We identified three risk factors for nonunion: (i) older age (OR = 2.29; 95% confidence interval [CI] 1.21–4.33), (ii) longer duration of SCID (OR = 1.02; 95% CI 1.00–1.04), and (iii) fracture site (distal femur), with OR (comparison distal femur) including distal tibia/fibula (OR = 0.14; 95% CI 0.09–0.24), proximal tibia/fibula (OR = 0.19; 95% CI 0.09–0.38), proximal femur (OR = 0.10; 95% CI 0.04–0.21), and hip (OR = 0.13; 95% CI 0.07–0.26). Nonunions resulted in multiple complications, with upwards of 1/3 developing a pressure injury, 13% osteomyelitis, and almost 25% requiring a subsequent amputation. Our data have identified a high‐risk population for fracture nonunion of older veterans with a long duration of SCID who sustain a distal femur fracture. In view of the serious complications of these nonunions, targeted interventions in these high‐risk individuals who have any signs of delayed union should be considered. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research. This article has been contributed to by US Government employees and their work is in the public domain in the USA.